Complete scintigraphic resolution of a bone metastasis after androgen-deprivation therapy - Çayır, Derya; Bozkurt, Mehmet; Gültekin, Salih Sinan; Turan, Aynur (Journal of Surgery and Medicine, 2019)
99mTc-methylene diphosphonate (MDP) whole body bone scintigraphy is a frequently used imaging method for the evaluation of the bone metastases of prostate cancer. Nuclear medicine imaging modalities are very valuable in terms of functional assessment and treatment response assessment of the malign lesions that cannot be detected by anatomic imaging methods. However, it is known that some scintigraphic studies may have a relatively limited role in defining resolution and anatomical details of the lesion, compared to some radiological imaging modalities. Androgen-deprivation therapy (ADT) alone is rarely effective for the treatment of bone metastases, on that account combined systemic therapies are often preferred. Here we present a rare case of prostate cancer with radiologically undetectable bone metastasis evident on scintigraphy that has disappeared after 18 months of ADT.